PRE REQUISITE STUDY ON APPLICATION OF HAZARD ANALYSIS CRITICAL CONTROL POINT MANAGEMENT SYSTEM FOR ON BOARD TUNA LONGLINER - Budhi Hascaryo Iskandar; Gina Almirani Wahyudi; Tri Wiji Nurani (Research Center for Fisheries, 2011)
Along with the era of globalization and free market an approach for managing quality through testing the final product is considered not able to meet consumer demands. It drives to a new approach based on prevention and control efforts during the process. Hazard analysis critical control point quality management system is considered appropriate because it can prevent the distortion and instead of waiting until the problems arise. The process of handling the fish on the boat as a part of the production chain affects the quality of tuna products, so the application of the hazard analysis critical control point quality management system on board tuna longline is considered important. Effectiveness of hazard analysis critical control point implementation as a quality system control is affected by sanitation standard operating procedure and good handling processing as the basic requirements (pre requisite), where the assessment can be a measure of readiness hazard analysis critical control point implementation. The purpose of this study is to determine the feasibility of the basic requirements of hazard analysis critical control point implementation in the tuna longline vessels. The research has been carried out by taking 10 samples of tuna longline vessels in the Nusantara Fishing Port of Pelabuhan Ratu and Samudera Fishing Port of Nizam Zachman, Jakarta. The basic requirements of eligibility conditions on longline vessels fishing in the port are pretty good. Results showed general assessment Y values are in the range of 2d”Y<4. This can be concluded that the applications of a pre requisite in sanitation standard operating procedure and good handling processing on tuna longline vessels in the both fishing ports were quite close to the standard, but improvements are still needed